Acridine orange for diagnosis of malaria Our experience (South East Asia Journal of Public Health, 2016)
Light microscopy of Romanowsky stained peripheral blood smear examination is the age old and commonest method for laboratory diagnosis of malaria. However it is labor intensive, time consuming and requires qualified personnel. So fluorescent microscopy variation that is Quantitative Buffy Coat method( QBC) came into vogue. But QBC imposes cost limitation despite its high performance. Therefore we decided to evaluate fluorescent method using acridine orange in our set up. In this study we have compared Acridine Orange staining with Leishmans staining as gold standard. The sensitivity and specificity of acridine orange was 99.28% and 97.19% respectively, while positive predictive value (PPV) and negative predicitive value was 89.93% and 99.82% respectively.South East Asia Journal of Public Health Vol.6(1) 2016: 49-51